THE PLACE AND IMPORTANCE OF THE INTEGRATIVE APPROACH IN PRIMARY CLASSES - Norova Nargiza daughter of Khalmamat (Western European Studies, 2024)
This article shows how important it is to conduct lessons in primary classes based on an integrative approach and how important the role of interlinking subjects in the education system is. The methodology of the integration of disciplines was developed, suggestions and recommendations were given.
Keywords: Primary education; integrative approach; competence; communication